PEDAGOGICAL FOUNDATIONS FOR DEVELOPING A HEALTHY LIFESTYLE CULTURE IN THE DIGITAL EDUCATIONAL ENVIRONMENT (BASED ON A PHYSIOLOGICAL APPROACH) (International Conference on Education, Psychology and Humanities, 2026)
The formation of a healthy lifestyle culture has become a strategic educational objective in the context of digital transformation, changing student behavior, and the growing prevalence of sedentary habits. From a physiological perspective, healthy lifestyle culture is connected with the regulation of movement, nutrition, sleep, stress, recovery, and self-care behaviors that directly influence the functional state of the body. The purpose of this thesis is to substantiate the pedagogical foundations for developing a healthy lifestyle culture in the digital educational environment on the basis of a physiological approach. The study applies theoretical analysis, comparative interpretation, and synthesis of international documents and recent research on physical activity, self-care, digital health, e-health literacy, and digital interventions targeting student lifestyle behavior. The findings show that the pedagogical effectiveness of the digital educational environment depends on its ability to support informed choice, behavioral self-regulation, continuous feedback, and balanced digital use rather than passive information consumption. The thesis argues that a physiological approach gives educational work a measurable foundation because it links value-oriented healthy behavior with observable bodily functions and daily regimes. It is concluded that healthy lifestyle culture in digital education should be developed through an integrated model combining health knowledge, digital literacy, reflective self-monitoring, and pedagogically controlled digital tools.
Keywords: healthy lifestyle culture, digital educational environment, physiological approach, self-care, physical activity, e-health literacy, digital health, pedagogical foundations